Residential livability, privacy and life satisfaction among residents of low- cost housing in Jigawa State, Nigeria - Bashari, Sunusi (2020)
Residential livability is the ability for a residential area to provide basic facilities and amenities to support residents’ life satisfaction. The characteristics that are normally associated with low-cost housing in Nigeria are poor architectural standard, poor and structurally unsound construction with absent or inadequate services such as infrastructural and social amenities. Livability concept is normally based on culture, however, less attention was given to this aspect in house building especially low-cost housing. This study focused on the influence of residential livability dimensions on life satisfaction among the residents of low-cost housing in Jigawa state, Nigeria. This study also examined the moderating effect of privacy as one of the important cultural elements in housing design on the relationship between residential livability dimensions and life satisfaction of the residents. The researcher used a mixed-methods approach guided by QUAL-Quan Model developed by Creswell (2015). For the qualitative study, the researcher used phenomenology design, using Focus Group Discussions (FGD) and in-depth interview with residents. A total of 19 residents involves as participants in this part of the study where 8 residents for FGD and 7 residents together with 4 housing officials who were responsible for all housing issues in Jigawa State for an in-depth interview. Meanwhile, a quantitative study was based on survey design whereby the questionnaire was administered to 375 respondents. The retrieved 372 questionnaires from residents were subjected to SPSS and AMOS software for analysis. Through FGD, five dimensions of residential livability were identified which are; dwelling unit features, social environment factors, physical environment factors, safety and crime indicators and functional environment factors. The findings revealed, that the design of public low-cost housing does not reflect the culture of the state, because the design of these housing estates was imported from foreign countries. As such privacy of the residents were not properly taken care due to the limited number of bedrooms, toilets, bathroom and lack of fencing. Furthermore, the results from the survey indicated a low level of life satisfaction among residents of low-cost housing in Jigawa State, Nigeria. The result also revealed that, there exists a strong positive relationship between the four residential livability dimensions with life satisfaction among the residents of public low-cost housing in Jigawa State. The four dimensions are dwelling unit feature, social environment, the physical environment and functional environment. Structural Equation Modelling (SEM) output revealed that all the four dimensions of residential livability (considered in this study) were found to be significant with life satisfaction and also predicts life satisfaction among the residents of low-cost housing in Jigawa State. In addition, the finding revealed that, there were moderating effects of privacy in the relationship between the dwelling unit and life satisfaction. The study concludes that life satisfaction of the residents of low-cost housing in Jigawa State will be improved if the low-cost housing provided is highly livable and privacy is taken care of in the design of the housing.